Hakikat Wahyu Perspektif Manna Al-Qathan - Qimanullah, Abdul Malik; Sanah, Siti (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
The Qur'an is a holy book and the main source of teachings for Muslims containing the word of Allah SWT, revealed to the Prophet Muhammad SAW as revelation through the intermediary of the Angel Gabriel. The process of receiving the revelation is unique and exclusive, occurring when the Prophet is conscious or through a real dream. Revelation, in this context, is fundamentally different from inspiration and instinct, although all three can be understood as forms of